Proposal of a traceability 4.0 system in Renault CACIA using blockchain technologies - Costa, Diogo Filipe Duarte (2022)
Increasing popularity of cryptocurrencies lead to the rapid development of blockchain-based distributed ledger keeping systems. Industrial applications for the new technologies were soon found, enhanced by needs of security, trust and transparency along the value-chain in traceability of products, parts and processes, particularly when transactions are being maintained through several different entities. Traceability solutions are also increasingly being built upon IoT or IIoT platforms. Although this allows for highly modular and flexible architectures, severe security deficiencies make these designs inapplicable to most real-life production lines. Lack of research and practical advances in the creation of modular and easily deployable frameworks motivated development of the project underlying this dissertation.